STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK SIKAP TOLERANSI BERAGAMA SISWA DI SMA NEGERI 7 MALANG - Syahna Thousahilwa; Mochamad Nurcholiq (Journal Islamic Studies, 2025)
The values of tolerance in social life need to be formed through education, including in the context of learning Islamic Religious Education (PAI). This study aims to describe the form of mutual respect in religion as well as the strategies of PAI teachers in instilling the value of tolerance among students. This study aims to analyze the form of students' religious tolerance attitude and identify the strategies of PAI teachers in building tolerance character at SMAN 7 Malang. This study used a descriptive qualitative approach with field research method. Data collection was conducted through observation, interviews, and documentation, involving the principal, PAI teachers, and students. Data analysis included data reduction, data presentation, and verification using source triangulation. The research findings show two main aspects: (1) The form of students' inclusive attitude includes mutual respect for religious differences, freedom of belief, and fair and good behavior among others; (2) PAI teachers' strategies in instilling tolerance include habituation (intra- and extracurricular), exemplary, and coaching.